Implications of the Development Potential of Solar Power Plants (PLTS) on Tri Hita Karana Sustainability in Denpasar City - I Nyoman Gede Adrama; I Gusti Ngurah Sudiana; I Made Girinata (Journal of Social Research, 2025)
This study explores the implications of Solar Power Plant (PLTS) development on the sustainability of Tri Hita Karana values in Denpasar City. Using a qualitative approach with case studies, in-depth interviews, and thematic data analysis, the research examines how solar energy aligns with Bali’s traditional values, including the spiritual, social, and environmental dimensions. The findings reveal that solar power supports the Parhyangan aspect by reducing carbon emissions and preserving nature, which is considered a manifestation of God’s greatness. In terms of Pawongan, the development of solar power creates job opportunities and enhances public awareness of clean energy. From a Palemahan perspective, it helps maintain ecological balance by minimizing the exploitation of fossil fuels and contributing to environmental conservation. The study concludes that integrating solar energy with Tri Hita Karana values can provide a sustainable development model that harmonizes modern technology with local cultural wisdom. However, challenges such as land constraints and public awareness need to be addressed to fully realize the potential of solar power in Denpasar. This research offers a unique framework for balancing technological advancement with cultural preservation in urban development.